Performance of Malaysian Islamic unit trust fund with the Syariah index in the 21st century / Noredayu Kahar - Kahar, Noredayu (2007)
This study investigates the investment performance of 10 Islamic unit trust funds in Malaysia in the new century. This research was conducted to see which unit trust funds performed better within that period by looking at the fund whether it is outperformed or underperformed the market benchmark. Syariah Index will be use in this study as a market benchmark. This study also includes the investigation on the funds manager's ability in making investment decision in that period and investigation of the funds degree of diversification A few methods will be used to evaluate the performance that is Sharpe Index, Adjusted Sharpe Index, Jensen Alpha Index, Treynor Index and R2 Data will gather from various sources such as Bloomberg, Bank Negara Malaysia and The Edge.